2022
DOI: 10.1371/journal.pone.0268535
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-designed single molar dental prostheses: A protocol of prospective experimental study

Abstract: Background Dental prostheses, which aim to replace missing teeth and to restore patients’ appearance and oral functions, should be biomimetic and thus adopt the occlusal morphology and three-dimensional (3D) position of healthy natural teeth. Since the teeth of an individual subject are controlled by the same set of genes (genotype) and are exposed to mostly identical oral environment (phenotype), the occlusal morphology and 3D position of teeth of an individual patient are inter-related. It is hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that results with acceptable accuracy were obtained in a study aiming to design a single molar dental prosthesis that mimics the morphology of a natural healthy tooth by learning the tooth characteristics from the remaining teeth, thanks to a developed AI algorithm. According to the results of this study, the applicability of artificial intelligence in the design of single-molar dental prostheses has been demonstrated, and it has been emphasized that the accuracy of biomimetic artificial intelligence-designed dental prostheses can be further increased with further training and optimization of the algorithms [53].…”
Section: Prosthetic Dentistrymentioning
confidence: 85%
“…It has been reported that results with acceptable accuracy were obtained in a study aiming to design a single molar dental prosthesis that mimics the morphology of a natural healthy tooth by learning the tooth characteristics from the remaining teeth, thanks to a developed AI algorithm. According to the results of this study, the applicability of artificial intelligence in the design of single-molar dental prostheses has been demonstrated, and it has been emphasized that the accuracy of biomimetic artificial intelligence-designed dental prostheses can be further increased with further training and optimization of the algorithms [53].…”
Section: Prosthetic Dentistrymentioning
confidence: 85%
“…In addition, the number of cases will gradually increase as data is collected from future patients. Furthermore, a voxel-based 3D-CNN [36] on 3D seg-mented CBCT images will be useful in increasing the number of image features if more cases can be used as input data.…”
Section: Discussionmentioning
confidence: 99%
“…The main measurements were accuracy, area under the curve (AUC), and error rate. Most of the studies used generative adversarial networks [30][31][32] and knowledge-based systems [33,34]. No studies used available public dataset sources.…”
Section: Prosthodontic Treatment Planning and Prosthesis Designingmentioning
confidence: 99%